Reduction of outage probability due to handover by mitigating inter-cell interference in Long-Term Evolution networks - Hussein, Yaseein Soubhi; Mohd Ali, Borhanuddin; A. Rasid, Mohd Fadlee; Sali, Aduwati (Electronics and Telecommunications Research Institute, 2014)
The burgeoning growth of real-time applications, such as interactive video and VoIP, places a heavy demand for a high data rate and guarantee of QoS from a network. This is being addressed by fourth generation networks such as Long-Term Evolution (LTE). But, the mobility of user equipment that needs to be handed over to a new evolved node base-station (eNB) while maintaining connectivity with high data rates poses a significant challenge that needs to be addressed. Handover normally takes place at cell borders, which normally suffers high interference. This inter-cell interference (ICI) can affect HO procedures, as well as reduce throughput. In this paper, soft frequency reuse (SFR) and multiple preparations (MP), so-called SFRAMP, are proposed to provide a seamless and fast handover with high throughput by keeping the ICI low. Simulation results using LTE-Sim show that the outage probability and delay are reduced by 24.4% and 11.9%, respectively, over the hard handover method — quite a significant result.